Variation in Drought‐Tolerance Components and their Interrelationships in the Minicore Collection of Finger Millet Germplasm. Issue 4 (1st July 2016) - Krishnamurthy, L.; Upadhyaya, Hari D.; Kashiwagi, J.; Purushothaman, R.; Dwivedi, Sangam L.; Vadez, V.
Abstract : Finger millet [ Eleusine coracana (L.) Gaertn.] is an important and nutritious cereal cultivated largely in the tropics of Africa and Asia. It is adversely affected by intermittent droughts, and a trait‐based selection for drought tolerance is expected to enhance yield stability. The current work has segregated the shoot biomass as total water use ( T ) and transpiration efficiency (TE) and assessed the importance of these components and their association with drought tolerance. A major part of the minicore collection of finger millet germplasm ( n = 69) was evaluated in mini‐lysimeters for the variation in T and TE under both terminal drought‐stress (DS) and well‐watered (WW) environments. Contribution of T to shoot biomass under drought was minor but that of TE was large and positive. Both T and TE positively influenced the shoot biomass production. Total water use explained the shoot biomass variation more when WW, whereas TE explained more variation under DS. Under DS, the minicore germplasm accessions varied in shoot biomass by 0.5‐fold, T by 0.16‐ to 0.36‐fold, and the TE by twofold. Categorization of the finger millet germplasm for TE differentiated accessions, into high and low groups, each with 11 accessions. No distinct or useful race or sub‐race‐specific variation was found for T, TE, or the total shoot biomass productivity among the four races of finger millet. Selection and incorporation of both T and TE would enhance the efficient use of water and yield stability.